Status Free Trade Zone Kota Batam Dalam Persepktif Ekonomi Pertahanan - Budiman, Diky (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
The purpose of this study is to understand the condition of Batam City with the status of free trade zone and also to look at the achievement of that status with economic defense persepctive. This study used qualitative method. The result is Batam City with the status of free trade zone are changed such as their rules, the facilities of infrastructure to support the status, while Batam’s economic growth has so far remained stagnant, investment in foregin direct investment has been achived as expected, but must be observed so that there is no dependence on foreign parties. Exports have decreased, while import have increased, export and import activites of Batam City are depended on the port system, while the exsiting system is still not good. In addition, the growth of labour is not accordance with the amount of employment available in Batam City, it is feard to be a threat.Keywords: Free Trade Zone; Economic Defense; Batam City.